The Influence of Religious Knowledge and Farmers’ Economic Welfare on Cassava Selling Practices in Gadut - Zulkarnain, Muhammad; Hendri, Novi; Wirman, Hardi Putra (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
This study aims to analyze how the dynamics of religious knowledge play a role in shaping the level of economic welfare of farmers involved in the practice of selling cassava without weighing in Nagari Gadut. This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis technique as the main method to test the causal relationship between latent variables, namely Farmers' Religious Knowledge and Farmers' Economic Welfare in Cassava Sales Practices. The results show that construct X1 (Farmers' Religious Knowledge) is proven to have a significant negative effect on Y (Cassava Sales Practices), while X2 (Farmers' Economic Welfare) has a positive but insignificant effect. Although the model is quite good, it is still necessary to evaluate the high multicollinearity indicators and the addition of other variables to strengthen the model's explanatory power.